Transparansi Pengelolaan Badan Usaha Milik Desa Dalam Rangka Optimalisasi Kontribusi Pada Perekonomian Daerah - Subhan Ashary Rezky Sanaky (Faculty of Law, Universitas Pattimura, 2021)
In an optimal and good regional economy, management of BUMD is very important. One of the good management of BUMD is through the principle of transparency. This principle is very important. Management by using the Transparency Principle in the management of this BUMD must be carried out, so that the BUMD can achieve the objectives of the establishment of the BUMD. That is supporting the economy of a region and also contributing to the economy of the region. The method for this research is descriptive analytical with normative juridical research using primary, secondary and tertiary data through literature and document studies. The results showed that the importance of managing BUMD in transparency through the principle of transparency is also the best way that can be done by BUMD to be able to fight crime that occurs within BUMD itself, which is often still done by parties certain parties to benefit from the management of BUMD that does not use the principle of transparency. Transparency is also an important point in the management of BUMD to be able to realize the tangible manifestation of improved management of management and implementation of BUMD that is good and can also help in reducing opportunities for occurrence corruption, collusion and Nepotism that continue to occur in the management of BUMD.